Ejercicios respiratorios y sus beneficios en la recuperación de pacientes de 40 a 60 años Post Covid en el Hospital Martin Icaza. Diciembre 2022 – abril 2023 - Pincay Montece, Alin Norbelis (2023)
Breathing exercises avoid complications of post covid-19 sequelae, their function is to increase strength and resistance to reduce respiratory distress, prevent postural defects and increase flexibility and thoracic mobility. The objective was to determine the effectiveness of breathing exercises and their benefits in the recovery of patients from 40 to 60 years old Post Covid-19 treated at the Martín Icaza Hospital during the period December 2022 - April 2023. The methodology was quantitative descriptive, analytical of cross type. -non-experimental, observational, retrospective sectional design, the analysis of the clinical history allowed us to demonstrate the clinical characteristics of 45 post-covid-19 patients, a 5-item survey was applied to them. Results: The male sex predominated with 53% with an age range of 50 to 60 years 31%, urban area 73%, 40% had diabetes mellitus 40%, hypertension 36%, 78% were infected at some time, 62% with mild infection, post covid -19 sequelae were tachycardia 27%, loss of taste and smell 33%, headache 25%, anxiety 60%, back pain 29%, myalgia 24%, other sequelae include dyspnea 33%, cough 27%, 72% They have reduced their daily routine. activities, 56% have not received respiratory physiotherapy, and 56% do not perform physical exercises. Conclusions: The main perceived post-covid-19 sequelae are neurological, musculoskeletal and others, associated with covid-19 pathologies and severity, hospitals must guarantee comprehensive patient care with respiratory techniques and exercises that help control breathing and the dyspnea.